The financial accelerator mechanism: does frequency matter? - Claudia Foroni; Paolo Gelain; Massimiliano Marcellino (European Central Bank (ECB), 2022)
We use mixed-frequency (quarterly-monthly) data to estimate a dynamic stochastic general equilibrium model embedded with the financial accelerator mechanism a la Bernanke et al. (1999). We find that the financial accelerator can work very differently at monthly frequency compared to the quarterly frequency, i.e. we document its inversion. That is because aggregating monthly data into quarterly leads to large biases in the estimated quarterly parameters and, as a consequence, to a deep change in the transmission of shocks.
Keywords: C52; E32; E52; 330; DSGE models; financial accelerator; Mixed-frequency data